ПРАВОВЕ ВИХОВАННЯ У СПАДЩИНІ В. СУХОМЛИНСЬКОГО (Педагогіка вищої та середньої школи, 2007)
The article made an attempt based on the analysis pedagogical heritage of V. Sukhomlinsky to reveal it views on the problem of legal education and its relationship with other directions of personality education.